Indoor, outdoor, and personal exposure to PM2.5 and associated health risk in community-dwelling elderly residents in Fuzhou city, 2021: a cross-sectional study - Shuling KANG; Xin LIN; Kan LIN; Baoying LIU; Chuancheng WU; Jianjun XIANG; Jingwen CHEN; Quan ZHOU (Zhongguo gonggong weisheng)
ObjectiveTo investigate personal total, indoor, outdoor exposure to particulate matter less than 2.5 μm in aerodynamic diameter (PM2.5) and health risks associated with the exposure among community-dwelling elderly in Fuzhou city. MethodsA total of 247 residents (≥ 60 years of age, living at the current residence for at least 3 years, without serious respiratory/circulatory disease and without disability) were recruited from a community in Fuzhou city, Fujian province, using random sampling stratified by residential floor. Three-day continuous sampling of PM2.5 was performed by using a personal particulate sampler, a constant-temperature, constant-flow particulate sampler in the living room, and an automatic outdoor particulate sampler within 2 km of the participants' homes during the winter season for 140 participants and during the summer season for 107 participants in 2021. All participants were interviewed with a questionnaire on demographics, living conditions, health status, lifestyle behaviors, and activities during the PM2.5 sampling period. PM2.5 concentration was measured with the weighing method; polycyclic aromatic hydrocarbons (PAHs) and metal elemental components in collected PM2.5 were determined by ultra-high performance liquid chromatography and inductively coupled plasma mass spectrometry. The health risk associated with PAHs and metals in PM2.5 was assessed by using the health risk assessment model recommended by the United States Environmental Protection Agency. ResultsThe mean daily exposure concentrations of PM2.5 for the participants were 61.83 µg/m3 for personal exposure, 41.37 µg/m3 for indoor exposure, and 32.00 µg/m3 for outdoor exposure, with descending order of personal, indoor, and outdoor exposure concentrations. The total personal PM2.5 exposure concentration was higher in summer than in winter (71.78 µg/m3 vs. 50.72 µg/m3), while the personal indoor and outdoor PM2.5 exposure concentrations were lower in summer than in winter (indoor: 38.43 µg/m3 vs. 49.76 µg/m3, outdoor: 32.00 µg/m3 vs. 34.53 µg/m3). When personal indoor and outdoor PM2.5 concentrations were low (indoor < 57.95 µg/m3, outdoor < 49.38 µg/m3), the total personal exposure concentrations were significantly higher than the personal indoor and outdoor exposure concentrations; when personal indoor and outdoor PM2.5 concentrations were high, the total personal exposure concentration was close to the personal indoor and outdoor exposure concentrations. The health risks of exposure to PAHs and metal constituents in PM2.5 were higher for total personal exposure than for personal indoor and outdoor exposure, and higher in winter than in summer. Exposure to PAHs in PM2.5 posed a potential carcinogenic risk to the participants, with excess lifetime cancer risks (ELCRs) of 12.74 × 10 – 6 and 1.673 × 10 – 6 for winter and summer exposure, respectively. Exposure to manganese, arsenic, and cadmium in PM2.5 posed non-carcinogenic risks to the participants, all with health quotients greater than 1. Exposure to arsenic, nickel, cadmium, and lead in PM2.5 posed potential carcinogenic risks to the participants, with ELCRs of 128.272 × 10 – 6 and 226.214 × 10 – 6 for summer and winter arsenic exposure, respectively. ConclusionsWhen indoor and outdoor PM2.5 concentrations are low, taking indoor and outdoor concentrations as a surrogate for total personal exposure concentrations will underestimate actual personal exposure; when indoor and outdoor PM2.5 concentrations are high, using indoor and outdoor concentrations may approximate total personal exposure. Health risk assessment based on accurate personal exposure to PM2.5 and its constituents can reduce the bias in population health effects caused by inaccurate exposure assessment.